PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBANTUAN APLIKASI PIXTON PADA MATERI INDONESIA KAYA HAYATINYA - Nadia Rusheryanti; Wawan Syahiril Anwar; Ade Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop digital comic learning media assisted by the Pixton application on the material of Indonesia Kaya Hidupnya and to determine the feasibility of digital comic learning media. The method used is Research and Development using the ADDIE model. Validation tests were carried out on media experts, language experts, and material experts. Implemented in class V with 35 students. The results of the study showed that the digital comic learning media developed had a very feasible category, with media experts 100% "Very Feasible", language experts 94% "Very Feasible", lecturer material experts 88% "Very Feasible", teacher material experts 92% "Very Feasible" teacher responses 90%, and student responses 91%. Based on the results of the study, it can be concluded that the digital comic learning media assisted by the Pixton application developed is very feasible to be used as a learning medium in schools.